PREVENTION OF INFECTIOUS DISEASES - Israilova Saksiba Burivayevna; Jurev Shavkat Abdulvoxidovich (Western European Studies, 2024)
This article examines advances in infectious disease prevention strategies, including vaccinations, health care, hygiene regulations, and medical research. Through the study of historical and contemporary literature, the article aims to provide comprehensive insight into effective prevention methods and their impact on public health
Keywords: Infectious diseases; prevention; vaccination; health